Pendekatan Komunikasi Partisipatif Tim Samurai terhadap Family Caregiver dalam Transformasi Penanganan Pasung ODGJ - Rafly Putra Pratama; Sri Wahyuningsih (Jurnal Riset Komunikasi (JURKOM), 2025)
Highlighting the participatory communication approach applied by the Samurai team in the Selempang Mera Aba Idi program, Omben health center. The program pioneered the implementation of mental health programs in Sampang Regency, through Kadinkes Certificate No. 188/005/434.203/2020 regarding the replication of the Selempang Mera innovation. The study aims to identify and understand the participatory communication approach taken by the Samurai team towards family caregivers in the transformation of handling ODGJ confinement, through qualitative methods with observation, interviews and documentation. Using George Herbert Mead symbolic interaction theory, with three main key concepts of mind, self, and society. The results showed that the participatory communication approach significantly contributed to building family caregiver awareness about the importance of humane care and empowering ODGJ to live more efficiently, productively, and independently. The participatory communication approach of the samurai team, such as open dialog, collaboration of community and religious leaders, and inclusive and sustainable education. Thus, providing practical insights that can be adopted by health agencies in other regions. Keywords: Family Caregiver, Participatory Communication, ODGJ, Mental Health Program.